PREDICTION OF POTENTIAL MUTATION OF CHICKEN CORONAVIRUS INTO FUTURE HUMAN CORONAVIRUS BASED ON SPIKE S1 GLYCOPROTEIN GENE - HUSSEN, SHEKHMOUS H.; HUSSEIN, SHERZAD M.; MUSTAFA, SARBAST I.; ISA , RENAS H.; BARWARY, MWAFAQ S. (Journal of Duhok University, 2021)
The high mutation rates of the chicken coronavirus (IBV) cause economic threats to the poultry industry. However, the most dangerous situation is the likelihood of changing its sequences into human coronavirus (COVID-19-like virus). Therefore, in the present study we aimed to investigate the possibility of genetic mutation of IBV to COVID-19. Thus, the sequences of Spike (S1) Glycoprotein genes of both IBV and COVID-19 were aligned, analyzed and calculated to predict the possible changes that could happen in the sequences of S1. The results indicated that in the case of an independent function of probability of each cluster of S1 sequences, the potential mutation rate in the sequences of IBV to be as COVID-19 was equal to 1.87E-96. However, because the tendency for some sequence clusters of S1 gene was low or equal to zero, it is unattainable to mutate the chicken IBV into COVID-19 sequence. Furthermore, in case of the dependent function, the probability of assumed annual mutation to make IBV infectious for human may reach up to around 50% after about 260 years. As a conclusion, the mutating of chicken coronavirus into COVID-19-like virus is not impossible, but it might take a substantial period of time